2008
DOI: 10.1007/s10681-008-9740-3
|View full text |Cite
|
Sign up to set email alerts
|

Fiber initiation development in Upland cotton (Gossypium hirsutum L.) cultivars varying in lint percentage

Abstract: The ovules at the stage of fiber initiation from -1 to +1 days post-anthesis (dpa) were studied, using scanning electron microscopy (SEM), in five Upland cotton (Gossypium hirsutum L.) cultivars varying in lint percentage from 28.53% to 43.10%. Our results indicated that on -1 days post-anthesis (-1 dpa), fiber cell protrusions were found in all cultivars, but these protrusions varied among different materials and the differences did not correlate with ultimate lint percentage of each cultivar. At 0 days post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The cotton fiber's secondary wall thereby thickens to 3–6 m [ 51 ]. In some G. hirsutum cultivars, the thickness of trichome protrusion and fiber initiation are both highly correlated with the lint index and lint percentage [ 52 ]. Following initiation, the fiber begins to elongate between 2 to 20 DPA (Days Post Anthesis).…”
Section: Discussionmentioning
confidence: 99%
“…The cotton fiber's secondary wall thereby thickens to 3–6 m [ 51 ]. In some G. hirsutum cultivars, the thickness of trichome protrusion and fiber initiation are both highly correlated with the lint index and lint percentage [ 52 ]. Following initiation, the fiber begins to elongate between 2 to 20 DPA (Days Post Anthesis).…”
Section: Discussionmentioning
confidence: 99%
“…The density of fiber initials is generally considered an indicator of cotton yield [ 9 ] and a potential target for improving yield by biotechnological manipulations [ 5 ], although one claim to the contrary has been made [ 10 ]. More recent work demonstrated that a higher density of fiber initials presumably caused by higher auxin levels in the ovule epidermis at the fiber initiation stage resulted in higher fiber yield and finer fibers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber development occurs 3 days before and after anthesis coupled with enlargement of epidermal cells and protrusion of trichomes. Both the lint percentage and lint index are positively associated with the density of trichome protrusion (0 DPA) and fiber initials (1 DPA) in some cultivars of G. hirsutum ( Li et al, 2009 ). Elongation of the fiber starts within a period of 2DPA to 20DPA, followed by initiation.…”
Section: Cotton Fiber Developmental Biologymentioning
confidence: 99%